Atrial fibrillation in dilated cardiomyopathy: Outcome prediction from an observational registry. (15th January 2021) - Nuzzi, Vincenzo; Cannatà, Antonio; Manca, Paolo; Castrichini, Matteo; Barbati, Giulia; Aleksova, Aneta; Fabris, Enrico; Zecchin, Massimo; Merlo, Marco; Boriani, Giuseppe; Sinagra, Gianfranco
Abstract: Background: Little is known about the role of different types of atrial fibrillation (AF) in dilated cardiomyopathy (DCM). We investigated the epidemiological and prognostic impact of different types of AF in DCM during long-term follow-up. Method: We evaluated consecutive DCM patients enrolled in the Trieste Muscle Heart Disease Registry. Uni- and multivariable, extended Kaplan-Meier and propensity score-matching analyses were performed for a composite outcome including death/heart transplantation/ventricular-assist device implantation. Results: Out of 1181 DCM patients (71% males, age 49 ± 15 years, left ventricular ejection fraction 33 ± 11%), 46 (3.9%) had baseline permanent AF (permAF), while 66 (5.6%) had a history of paroxysmal/persistent AF. Compared with sinus rhythm (SR) patients, permAF patients were older (48 ± 15 vs. 61 ± 11 respectively, p = 0.001), were more frequently in NYHA class III-IV (18% vs. 30%, p = 0.002) and had larger left atrium diameter (40 ± 8 vs. 50 ± 10 mm, respectively). Paroxysmal/persistent AF patients had intermediate characteristics between permAF and SR. During a median follow-up of 135 (75–210) months, 63 patients developed permAF (0.45 new cases/100patients/year). At multivariable analysis, permAF as a time-dependent variable was an independent outcome predictor (HR 2.45; 95% C.I. 2.61–3.63, p < 0.001), together with creatinine, NYHA class, restrictive filling pattern and moderate-severe mitral regurgitation, while paroxysmal/persistent AF was neutral. Propensity score-matching analysis confirmed the higher rate of primary outcome events in patients with baseline or incident permAF versus patients without permAF during a very long-term follow-up (70% vs. 20%, p < 0.001). Conclusions: PermAF in a large DCM cohort had low prevalence and incidence but had a relevant. prognostic role on hard outcomes. Graphical abstract: Patients with non-dilated left atrium and without permAF (upper figure) are those with the best prognosis. LA enlargement (middle figure) is associated with adverse outcome. The worst prognosis is proper of patients with permAF at baseline (bottom figure) or incident at follow-up. Patients with dilated atria are at higher risk for permAF incidence. The arrow on the right represents the prognosis (green: favourable outcome; red: adverse outcome). Legend. LA: left atrium. Unlabelled Image Highlights: DCM is a particular HF setting where AF is relatively infrequent. The prognostic role of AF depends on the type of AF. Paroxysmal or persistent AF do not significantly affect prognosis. Permanent AF, at baseline or incident, carries a relevant negative prognostic impact. Dilated atria increase the risk of permanent AF incident.